Explicating Affordances: A Conceptual Framework for Understanding Affordances in Communication Research. Issue 1 (26th December 2016) - Evans, Sandra K.; Pearce, Katy E.; Vitak, Jessica; Treem, Jeffrey W.
Abstract: This study aims to clarify inconsistencies regarding the term affordances by examining how affordances terminology is used in empirical research on communication and technology. Through an analysis of 82 communication‐oriented scholarly works on affordances, we identify 3 inconsistencies regarding the use of this term. First, much research describes a particular affordance without engaging other scholarship addressing that affordance. Second, several studies identify "lists" of affordances without conceptually developing individual affordances within those lists. Third, the affordances perspective is evoked in situations where the purported affordance does not meet commonly accepted definitions. We conclude with a set of criteria to aid scholars in evaluating their assumptions about affordances and to facilitate a more consistent approach to its conceptualization and application.